2018
DOI: 10.1186/s12906-018-2145-5
|View full text |Cite
|
Sign up to set email alerts
|

Rhaponticum acaule (L) DC essential oil: chemical composition, in vitro antioxidant and enzyme inhibition properties

Abstract: Backgroundα-glucosidase is a therapeutic target for diabetes mellitus (DM) and α-glucosidase inhibitors play a vital role in the treatments for the disease. Furthermore, xanthine oxidase (XO) is a key enzyme that catalyzes hypoxanthine and xanthine to uric acid which at high levels can lead to hyperuricemia which is an important cause of gout. Pancreatic lipase (PL) secreted into the duodenum plays a key role in the digestion and absorption of fats. For its importance in lipid digestion, PL represents an attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Mosbah et al. () have previously reported that rhaponticum acaule (L) DC essential oil had pancreatic lipase inhibitory activity with IC 50 ranging between 20.9 and 25.9 mg/mL. Zhang and Lu () have also reported that petroleum ether extract from Cleistocalyx operculatus flower buds show high pancreatic lipase inhibitory activity with IC 50 of 38.65 μg/mL.…”
Section: Resultsmentioning
confidence: 97%
“…Mosbah et al. () have previously reported that rhaponticum acaule (L) DC essential oil had pancreatic lipase inhibitory activity with IC 50 ranging between 20.9 and 25.9 mg/mL. Zhang and Lu () have also reported that petroleum ether extract from Cleistocalyx operculatus flower buds show high pancreatic lipase inhibitory activity with IC 50 of 38.65 μg/mL.…”
Section: Resultsmentioning
confidence: 97%
“…var. pungens [ 89 ], Rhaponticum acaule (L.) DC [ 90 ], Acacia mollissima and Acacia cyclops [ 91 ] and Neolitsea kedahense Gamble [ 92 ] and Senna podocarpa (Guill. and Perr.)…”
Section: Effects and Possible Mechanisms Of Bcp On Diabetesmentioning
confidence: 99%
“…[ 93 ] containing BCP as a major constituent have shown α-glucosidase inhibitory activity. The essential oils obtained from the seeds, flowers, leaves, and/or stems of these plants characterized to contain BCP as one of the major components and attributed to display potent free radical scavenging, xanthine oxidase inhibition, metal chelating, and antioxidant activities, in addition to inhibition of α-glucosidase [ 90 ]. These plants rich in BCP were suggested useful in T2DM, obesity, and hyperlipidemia in many studies [ 90 ].…”
Section: Effects and Possible Mechanisms Of Bcp On Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to positive control tetrahydrolipstatin (IC 50 0.16 mg/mL), RAEO was less potent. These promising results, especially α-glucosidase inhibition, make RAEO interesting as a treatment of metabolic disorders like type 2 diabetes [59].…”
Section: Rhaponticum Acaule Essential Oilmentioning
confidence: 99%